PENGARUH METODE READING GUIDE TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI SMP NEGERI 1 GEMPOL KABUPATEN CIREBON - Nur Hasanah; Asep Mulyana; Yunita Yunita (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2023)
The purpose of this study is to determine the influence of the reading guide method on learning motivation in social studies subjects, to determine the influence of the reading guide method on student learning outcomes in social studies subjects, and to determine the influence of the reading guide method on learning motivation and student learning outcomes in social studies subjects at SMP Negeri 1 Gempol, Cirebon Regency.This research is a quantitative research. The design of this study Quasi experimented using the nonequivalent posttest-onty control group design. The study population was 15 students from class IX H and 15 students from class IX I, totaling 30 students selected through random sampling. The instruments used in this study were in the form of tests, questionnaires, observations of learning activities and documentation. The results of this study show that, there is an influence of the reading guide method on learning motivation in social studies subjects with a Sig value of 0.003, there is an influence of the reading guide method on student learning outcomes in social studies subjects with a sig value of 0.012, and there is an influence of the reading guide method on learning motivation and student learning outcomes in social studies subjects with a p value (sig) of 0.451. this means that student learning motivation and learning outcomes are influenced by the reading guide method.